2022
DOI: 10.3390/biom12040585
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrinogen-like Domain of ANGPTL3 Facilitates Lipolysis in 3T3-L1 Cells by Activating the Intracellular Erk Pathway

Abstract: Background: ANGPTL3 stimulates lipolysis in adipocytes, but the underlying molecular mechanism is yet unknown. The C-terminal fibrinogen-like domain of ANGPTL3 (ANGPTL3-Fld) activates the AKT pathway in endothelial cells. Hence, we evaluated whether ANGPTL3-Fld stimulates lipolysis in adipocytes through the MAPK kinase pathway. Materials and Methods: 3T3-L1 adipocytes were treated with isoproterenol (ISO), ANGPTL3-Fld, or both. Lipolysis was evaluated through the release of free fatty acids (FFAs) in the cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…F. Baratta et al main causes of hepatic fat accumulation and central to the development of hyperlipidemia. Interestingly, this typical lipid profile might also depend on the reduced activity of lipoprotein lipase (LPL) due to an increased activity of ANGPTL3 and ANGPTL4, which represent the physiological circulating inhibitors of LPL [67][68][69]. Notably, plasma levels of ANGPTL3 and ANGPTL4 were found to be increased in obesity and T2DM as well as in NAFLD/NASH patients [70].…”
Section: Lipidsmentioning
confidence: 99%
“…F. Baratta et al main causes of hepatic fat accumulation and central to the development of hyperlipidemia. Interestingly, this typical lipid profile might also depend on the reduced activity of lipoprotein lipase (LPL) due to an increased activity of ANGPTL3 and ANGPTL4, which represent the physiological circulating inhibitors of LPL [67][68][69]. Notably, plasma levels of ANGPTL3 and ANGPTL4 were found to be increased in obesity and T2DM as well as in NAFLD/NASH patients [70].…”
Section: Lipidsmentioning
confidence: 99%
“…HSL, the major effector of lipolysis, is the downstream target of PKA ( Fig. 4E ) ( 22 , 23 ). Therefore, Western blotting was used to determine the effects of Amuc_1100 on the expression levels of different proteins and genes known to be related to lipolysis in vivo and in vitro ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 Such an effect could be explained by enhanced lipoprotein lipase activity in oxidative tissues and possibly reduced adipose tissue lipolysis, resulting in a reduced flux of FFA into the liver. For example, we recently found that the fibrinogen-like domain of ANGPTL3 enhances lipolysis in cultured adipocytes derived from 3T3-L1 cells, 42 raising the possibility that FHBL2 may result in a decreased rate of in vivo adipose tissue lipolysis. It is possible that all of these mechanisms in concert might prevent an imbalance between the synthesis of triglycerides and apoB within hepatocytes, thereby preventing the development of excessive hepatic lipid accumulation.…”
Section: Discussionmentioning
confidence: 99%